Morderstwo z życia wzięte. Autobiografizm w powieściach kryminalnych na przykładzie twórczości wybranych pisarek = A true-life murder. Autobiography in crime fiction of selected women writers - Stadnik, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to discuss the influence of autobiographical experience on the work ofcontemporary female authors of crime fiction. The article touches upon issues such as self-creation,professional and family history inspirations, auto-therapy and correlations with the theory of autobiography.
Keywords: powieść kryminalna; literatura; tematy i motywy